Operation of the industrial accelerator of electrons with minimum beam intensity - T. V. Kovalinska; V. I. Sakhno; Yu. V. Ivanov (Ядерна фізика та енергетика)
Problem of attracting the powerful industrial radiation technique for radiation modification of the medical solutions and research of methods for their application is being solved. The important step in solving this problem is radiation biological experiments with modified solutions. Their implementation requires modernization of radiation technique and bringing its parameters in accordance with the specific of such experiments. The ways of modernization of the powerful radiation setting for medical and biological works were investigated, including in-vivo.